Thermal performance evaluation and analysis of helium heat exchanger for cryogenic propellant launch vehicle. (June 2022) - Baek, Seungwhan; Lee, Jisung; Kim, Kyung-Seok; Shin, Dongsun; Lim, Hayoung; Kim, Junghan; Kim, Jonggyu; Kim, Munki; Lim, Byoungjik; Kim, Chae-hyoung; Han, Sangyeop; Cho, Kiejoo; et al.
Highlights: Helium heat exchanger for a liquid propellant launch vehicle tested in full scale. Experiments were performed with fuel-rich hot-gas and cryogenic helium as actual. The effectiveness ( ε ) was analyzed and predicted with helium inlet temperature. As the inlet temp. increase, the ε increased due to heat trans. coeff. change. The launch vehicle HEX may be optimized with the average ε and the weight. Abstract: A launch vehicle that operates using cryogenic liquid propellants will require a pressurization process for a propellant tank. Usually, helium stored at cryogenic temperatures passes through the engine, is heated, and pressurizes the tank. Low-temperature helium is heated in a heat exchanger using high-temperature combustion gas from an engine. For the accurate performance prediction and weight optimization of the launch vehicle, the performance of the heat exchanger should be evaluated before launching. This study presents an evaluation method for predicting the performance of a heat exchanger in a launch vehicle. The heat exchanger performance was measured at a constant helium flow rate under actual engine operating conditions. A numerical analysis model for predicting the heat exchanger performance was developed and compared to the test results. The tests were conducted at different inlet temperatures. The test results and analysis confirmed that the effectiveness increased with the inlet temperature. Further analyses revealed that a change in the heat transfer coefficient, as well as the inlet temperature, changed the effectiveness by 6%. To accurately predict the performance of the launch vehicle, it was necessary to accurately predict the change in the heat transfer coefficient with temperature. A design method for the heat exchanger of a launch vehicle was also discussed. The heat-transfer area and weight should be optimized under the required conditions.